2023
DOI: 10.4103/ijd.ijd_565_22
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction and Associated Factors in Women with Psoriasis

Abstract: Context: Psoriasis, a chronic inflammatory skin disease, may negatively affect sexual function; however, data on the sexual health of female patients with psoriasis in Vietnam are lacking. Aims: To assess the risk of sexual dysfunction (SD) and its associated factors in female patients with psoriasis who visited the Ho Chi Minh City Hospital of Dermato-Venereology from April 2020 to October 2020. Settings and Design: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Female patients had significantly lower sexual desire (question 2) and satisfaction with their sexual life (question 16) than controls. Similar findings were reported by Nguyen et al, who found additionally significantly worsened arousal and pain ( 33 ), whereas Türel Ermertcan et al – arousal and orgasm ( 31 ). Kuzriki et al also pointed to decreased desire as the one that is mainly affected ( 34 ).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Female patients had significantly lower sexual desire (question 2) and satisfaction with their sexual life (question 16) than controls. Similar findings were reported by Nguyen et al, who found additionally significantly worsened arousal and pain ( 33 ), whereas Türel Ermertcan et al – arousal and orgasm ( 31 ). Kuzriki et al also pointed to decreased desire as the one that is mainly affected ( 34 ).…”
Section: Discussionsupporting
confidence: 87%
“…In our study, we did not assess psoriasis activity and severity index (PASI) since it was an online survey however in other experiments the results are diversified. In the paper by Kędra et al there was a correlation between sexual problems and PASI in both sexes (39) (38), whereas the other one found higher PASI among female patients with significantly decreased FSFI score (33,38). In the study by Al Mazeedi and Türel et al, no significant difference was observed between patients with mild or severe psoriasis in terms of the quality of their sexual life (31, 40).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations